Analisis Budaya Keamanan Informasi di Puskesmas Kota Bandung - Syaza Syauqina; Puspita Kencana Sari; Adhi Prasetio; Candiwan Candiwan (Sekolah Vokasi Universitas Gadjah Mada, 2019)
Background : The use of information systems today has become a necessity in organizations, including in the health sector due to the large amount of patient data that must be managed. 95% of Bandung City citizens are entitled to health facility services in all health facilities that have been partnered with BPJS Kesehatan, one of which is the Puskesmas. In its service, the Puskesmas manages patient health data using computer-based SIM Puskesmas, thus personal health information is vulnerable to information security threats both from internal and external. Therefore, Puskesmas need to build information security to reduce the level of security violations and maintain the health information of their patients.Objective : The purpose of this study was to determine the factors that significantly influence the Culture of Information Security in Bandung Public Health Center.Methods : The research method used is a quantitative method with PLS-SEM data analysis technique using WarpPLS 6.0 software. The technique used is Model Evaluation consisting of Measurement Models, Structural Models and Hypothesis Testing. This research data uses primary data taken through questionnaires to 154 employees who were sampledResults : Based on the characteristics of the respondents it can be seen that the majority of health center employees are women, the highest age is 19-29 years, the most positions are Administration / Medical Records, Education of employees is S1, lenght of work of Employees is 1-5 years. In the information management process, the Puskesmas has used Computer Based. The Puskesmas has an Information Security Policy. Based on the Evaluation Model, it can be seen that the model is fit, because it meets the Rule of Thumb criteria.Conclusion : Based on the results of the Model Evaluation and Hypothesis Testing, it can be seen that the variables that influence the Information Security Culture in Bandung City Health Center are Management, Change Management, Knowledge, Soft Issue-Workplace Independent and Attitude.Keywords : Information Security Culture, Healthcare, PLS-SEM.